Pengaruh Kesadaran Pajak Terhadap Pembayaran Pajak STNK Tahunan - Andi Reskia Nur Hidayah; Ardiensyah Ardiensyah (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2025)
This study aims to help both the author and readers understand how tax awareness influences taxpayer behavior in paying the annual motor vehicle tax (STNK). Therefore, the researcher employed a descriptive qualitative approach using interview and observation techniques. This research explores the perspectives and experiences of several taxpayers in the Panakkukang District of Makassar City through interviews and direct observation. The findings of this study indicate that the level of tax awareness is significantly influenced by several factors, such as understanding of the function of taxes, perceptions of the services provided by SAMSAT, and the enforcement of penalties. It was also found that while most taxpayers are aware of the importance of paying taxes, there are still challenges in fostering public awareness regarding the annual STNK tax. These challenges include a lack of information about tax obligations and economic factors that influence timely payment decisions. These findings highlight the need for more effective communication strategies and participatory approaches to enhance public tax awareness and compliance